Honest People Tend to Use Less—Not More—Profanity: Comment on Feldman et al.'s (2017) Study 1. Issue 5 (July 2018) - de Vries, Reinout E.; Hilbig, Benjamin E.; Zettler, Ingo; Dunlop, Patrick D.; Holtrop, Djurre; Lee, Kibeom; Ashton, Michael C.
This article shows that the conclusion of Feldman et al.'s (2017) Study 1 that profane individuals tend to be honest is most likely incorrect. We argue that Feldman et al.'s conclusion is based on a commonly held but erroneous assumption that higher scores on Impression Management Scales, such as the Lie Scale, are associated with trait dishonesty. Based on evidence from studies that have investigated (1) self-other agreement on Impression Management Scales, (2) the relation of Impression Management Scales with personality variables, and (3) the relation of Impression Management Scales with objective measures of cheating, we show that high scores on Impression Management Scales are associated with high—instead of low—trait honesty when measured in low-stakes conditions. Furthermore, using two data sets that included an "I never swear" item, we show that profanity use is negatively related to other reports of HEXACO honesty-humility and positively related to actual cheating.